Factors affecting the decision to enroll in private health insurance among employees of the University of the Philippines - Morilla, Kevin E. (2009.)
This paper was designed to identify the factors affecting the decision of UPV employees to enroll in private health ensurance. Data were gathered through aq drop-off questionnaire with 117 study participants, 34 of whom were currently enrolled in private health insurance and 83 were not. Holders of private health insurance have longer years in school (16 years on average) than those without private health insurance (14 years on average) or have higher proportion of post post graduate units/post post graduate degrees (65% vs. 34%) Study participants with private health insurance were mostky females. The study participants with private insurance had a higher monthly income compared to study participants with out private health insurance (Php 15,519.00 vs. Php 12,061.00) Half of the study participant with and those without private health insurance can be described as moderately risk averse. Logistic regression analysis showe3d that the significant factors at 5% level of significance include years in formal school and at 1o percent level of significance include sex, alcohol consumption (proxy top risk averseness) and having asthma, chronic cough, pneumonia, tuberculosis, emphysema and any other respiratory or lung disorders (proxy to probability of illness occurring).
Thesis (Undergraduate, Bachelor of Sciencre in Economics) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2009.
Keywords: Health Insurance -- University of the Philippines Visayas